2016
DOI: 10.1177/0269216316628407
|View full text |Cite
|
Sign up to set email alerts
|

Patient and caregiver perspectives on managing pain in advanced cancer: A qualitative longitudinal study

Abstract: Background: Despite advances in treatment of pain in advanced cancer, it remains a major

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
65
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 66 publications
(68 citation statements)
references
References 31 publications
3
65
0
Order By: Relevance
“…In fact, the symptoms discussed most frequently by our participants—pain, fatigue and abnormal bowel movements—were similar to the top three severe symptoms revealed in the review—fatigue, loss of appetite and pain. As would be expected, our finding that patients associated changes in their symptoms with the worsening of their illness had also been found in other studies (Hackett, Godfrey, & Bennett, ; Luckett et al., ).…”
Section: Discussionsupporting
confidence: 91%
“…In fact, the symptoms discussed most frequently by our participants—pain, fatigue and abnormal bowel movements—were similar to the top three severe symptoms revealed in the review—fatigue, loss of appetite and pain. As would be expected, our finding that patients associated changes in their symptoms with the worsening of their illness had also been found in other studies (Hackett, Godfrey, & Bennett, ; Luckett et al., ).…”
Section: Discussionsupporting
confidence: 91%
“…Longitudinal interview studies reveal that pain is very dynamic and complex for patients, and that pain control is often a trial and error process that requires continuous work [25]. Neither pain relief nor expertise in pain management is secured once and for all.…”
Section: Meaningful Outcomes For Patientsmentioning
confidence: 99%
“…Most patients seem to determine whether their pain is controlled by whether or not they can perform activities or tasks and maintain relationships with family or friends. This outcome is what determines themselves as individuals [22,25,31]. Bender et al [2] identified that patients are keen to understand the cause of their cancer pain, what to expect, options for pain control (including addressing concerns about strong opioids), and how to cope with cancer pain including talking with others and finding help.…”
Section: Meaningful Outcomes For Patientsmentioning
confidence: 99%
“…23 Our own research has also shown that patients and their carers face daily dilemmas on the best way to balance pain relief with the adverse effects of analgesia and the consequent impact of both on daily activities. 24,25 Attitudes and knowledge of health-care professionals (HCPs) towards opioids is likely to influence the quality of information provided to patients 26 and the increasing complexity of opioid choices in end-of-life care may further reduce the confidence of non-specialist practitioners. 27 However, addressing the concerns of patients leads to improvements in pain control, 28 and this process relies on specific contexts that support behavioural change in patients, carers and professionals.…”
Section: Background Rationalementioning
confidence: 99%